Pengawasan Badan Permusyawaratan Desa Terhadap Pemerintah Desa dan Pelaksanaannya Terhadap Pembangunan di Desa Poto, Kecamatan Fatuleu Barat, Kabupaten Kupang - Saranti Oktoriani Hay; Kotan Y. Stefanus; Cyrilius W. T. Lamataro (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the regulation of the Village Consultative Body's (BPD) oversight of village government and its implementation concerning development in Poto Village, Fatuleu Barat District, Kupang Regency. The research aims to analyze how the BPD performs its oversight function in accordance with applicable regulations, the challenges faced during implementation, and the impact of this oversight on the success of village development. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation. The findings reveal that while the BPD plays a strategic role in ensuring transparency and accountability within the village government, its implementation faces challenges such as limited understanding of regulations among BPD members and insufficient resources. This study recommends training for BPD members, improved communication between the BPD and village government, and strengthened regulations to support more effective and sustainable development.